How MICE Experience Quality Shapes Destination Image through Dual Pathways - Malau, Grace Carolina; Pamjuji, Dian Dhany; Zarkas, Ilham Azmi; Masriyah; Kurnia, ⁠Lusi; Arif, Ahmad Bachtiar (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2025)
This study investigates how experience quality at a major MICE event shapes post-trip destination image by testing the mediating role of satisfaction within the emerging tourism setting of Lake Toba, Indonesia. Using survey data from 413 attendees of the Aqua Bike WorldChampionship and Partial Least Squares Structural Equation Modelling, the analysis demonstrates that experience quality significantly enhances satisfaction and directly improves destination image. Satisfaction also exerts a strong positive influence on destination image and partially mediates the relationship between experience quality and image. These findings validate a dual pathway model in which affective processes operate through satisfaction, while cognitive processes allow objective event attributes to shape destination image independently. The study advances theoretical understanding of MICE experience formation by demonstrating concurrent emotional and rational mechanisms. Practical implications highlight the need for planners to strengthen both experiential and functional quality elements to enhance Indonesia’s competitiveness as a growing MICE destination.